Hepatitis-like onset of systemic lupus erythematosus in a 9-year-old female patient - Nadbrzeżna, Justyna; Sudoł, Maria; Blecharz, Gabriela; Pilch, Bożena; Kowalska-Duplaga, Kinga (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease the etiology and pathomechanism of which remain unclear. This case report presents the diagnostic difficulties caused by the atypical manifestation of SLE in a nine-year-old girl. The finding of an isolated increase in liver enzymes initiated the differential diagnosis of liver disease. The occurrence of additional symptoms in the following months, such as recurrent episodes of urticaria, followed by joint pains, formed the basis for further search for the cause of the presenting complaints. Finally, a diagnosis of SLE was established on the basis of clinical symptoms and laboratory results, including the detection of a lupus anticoagulant. The treatment was initiated with good outcome. This case illustrates how diverse and atypical clinical manifestations with uncharacteristic laboratory results SLE can present with, which can cause diagnostic difficulties and contribute to delays in making a correct diagnosis and starting effective treatment.